A novel post-weld composite treatment process for improving the mechanical properties of AA 6061-T6 aluminum alloy welded joints. (October 2022) - Cheng, Jiwen; Zhang, Zhaodong; Dong, Xiaonan; Song, Gang; Liu, Liming
Abstract: The welded joint for a heat-treated aluminum alloy AA 6061-T6 showed softening in the fusion zone (FZ) and the heat-affected zone (HAZ). This paper proposed a post-weld composite treatment process that overcame the joint softening by coupling the solubilization treatment (ST), aging treatment (AT), and cold rolling (CR). Three post-weld composite treatment processes were investigated to reveal the effect of the interaction between precipitation hardening and work hardening on joint mechanical properties. Experimental results showed that the post-weld "ST-AT-CR" composite treatment process could improve the microhardness of the FZ and HAZ to the level of the original base metal (BM), and the joint strength and ductility could reach up to 100 % and 67 % of the BM, respectively. On the other hand, it was also observed that the post-weld "CR-ST-AT" composite treatment process could make the joint softening more serious. The higher pre-existing dislocation density by the CR process would provide more diffusion channels for the solute atoms during the ST-AT process and promote the over-aging of strengthening phases, while the ST-AT process would significantly reduce the pre-existing dislocation density.